The case for Israel - Dershowitz, Alan M. 1938- (Wiley, 2003)
One of America's leading attorneys offers an impassioned defense of the state of Israel, arguing that, although the country is not perfect, it remains the only outpost of democracy in the Middle East, answering critics who accuse Israel of being an imperialist power and documenting the facts about the nature of the conflict between Israel and the Palestinians.
Includes bibliographical references (p. 245-257) and index
Keywords: Palestijnse kwestie; Geschichte; Juden; Nahostkonflikt; Arab-Israeli conflict; Jewish refugees -- Palestine -- History; Jews -- Colonization -- Palestine; Jews -- Palestine -- History; Zionism; Zionists -- Palestine -- History; Beschuldigung; Palästinafrage; Expansionspolitik; Israel -- History; Israel